Determinants of purchase intention of halal cosmetic products among muslim females: evidence from Indonesia - Ciptadi; Mulyarahardja, Raymond; Adhitya, Afdal Gilang; Budiharga, Jessica Wirati Mula; Samuel, Yoel Putera (Journal of Halal Product and Research (JHPR), 2023)
Halal cosmetics market in Indonesia has gained more and more attention and is driving global demand growth. Halal cosmetics awareness among female young adults in Indonesia is increasing in line with the rapid growth projection of the Indonesian Halal cosmetics market. However, factors playing a significant role in their purchase intention to buy Halal cosmetic products remain ambiguous. Furthermore, there is no well-established study in Indonesia that explored the role of brand image, promotion, and Halal logo as predictors of purchase intention. This study aims to address this gap and analyze the predecessors and consequences of aforementioned factors towards the purchase intention of Halal cosmetics in Indonesia, specifically among young Muslim women. Samples in this study were obtained by means of quota sampling technique with a total of 289 female Indonesian Muslim respondents aged 21 - 40 years old. Likert-type scale anchoring five-points was used to record the responses. The scale of 1 indicates strong disagreement and 5 indicates strong agreement. The analysis was conducted through Exploratory Factor Analysis and Multiple Regression Analysis on SPSS. This study discovered that promotion is an essential predictor of purchase intention of Halal cosmetic products within the young Muslim adult population in Indonesia. Unexpectedly, brand image plays an insignificant role in purchase intention. Moreover, theory of planned behavior provided insight into a theoretical vulnerability of subjective norm as predictor of purchase intention. As this topic is predominantly researched in Malaysia, there has been little to no studies done on this particular context in Indonesia. This study's results are anticipated to provide meaningful contribution to the literature in evaluating the purchase intentions of Indonesian young Muslim women towards Halal cosmetics. Cosmetics brands and manufacturers may extract value from this study's results to sharpen activity focus on variables closer to purchase intention.